A computational study of surface tension determination of dense fluids as benzene, toluene, methanol, ammonia, ethylene, and carbon monoxide. (2nd January 2017) - Ashrafi, Fereydoun; Moeini, Vahid; Siami, Atena
ABSTRACT: In this study, the parameters of linear isotherm regularity, which called LIR equation state used to compute the surface tension of some dense fluids as benzene, toluene, methanol, ammonia, ethylene, and carbon monoxide. An expression has derived for radial distribution function (RDF) at constant temperature, g ( σ ), for a real fluid by the use of LIR. This expression, which is related to intermolecular interaction, can be used to describe the temperature–density dependency of RDF at constant temperature, g ( σ, ρ, T ). In addition, we derive an expression for surface tension of dense fluids (CO, C6 H6, C6 H5 CH3, CH3 OH, NH3, and C2 H4 ) using the LIR and g ( σ, ρ, T ). Unlike previous models, it has shown that, surface tension can obtain without employing ΔH and ΔS. Only P-V-T experimental data have been used to calculate the surface tension. Comparison of the calculated values of surface tension by LIR with the values obtained experimentally show this method is not precise. This problem has led us to try to obtain the expression for surface tension using the extended parameters A, B ( A and B are the temperature-dependent parameters which noticeably are depended on attraction and repulsion). The obtained result shows that the accuracy of this method is very high and quite admissible.